Carbon material polar functional group and electric field coupling-based CO2 adsorption and capture method
By orientedly grafting polar functional groups on the surface of the carbon-based adsorbent and combining the coupling effect of the applied electric field, the problem of difficult to balance the adsorption capacity, selectivity and regeneration energy consumption of existing CO2 adsorbent materials is solved, and high selectivity, large-capacity adsorption and low-energy regeneration of CO2 are achieved, thereby improving the overall energy efficiency of the CO2 adsorption and capture process.
Patent Information
- Application Number
- CN202411668096.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-07
AI Technical Summary
The existing CO2 adsorbent materials are difficult to take into account the adsorption capacity, adsorption selectivity and regeneration energy consumption, resulting in high CO2 capture costs and large energy consumption.
By grafting polar functional groups on the surface of the carbon-based adsorbent and combining the coupling effect of the applied electric field, high selectivity, large-capacity adsorption and low-energy regeneration of CO2 are achieved.
It improves CO2 adsorption capacity and selectivity, reduces regeneration energy consumption, achieves high efficiency and efficiency of the CO2 adsorption and capture process, and breaks through the current technical bottleneck of the coordination between efficient CO2 adsorption and low-energy regeneration.
Abstract
Description
Technical Field
[0001] The invention relates to a CO2 adsorption and capture method based on the coupling of polar functional groups of carbon materials with electric fields, belonging to the technical field of CO2 adsorption and capture. Background Art
[0002] CO2 capture, utilization and storage (CCUS) technology is regarded as a key technical path for the power industry to achieve near-zero CO2 emissions. In the CCUS technology chain, CO2 capture is not only the most expensive, but also consumes the most energy, and is the key link that determines system cost and energy efficiency. Therefore, the development of efficient and low-cost CO2 capture processes is crucial to promoting the widespread application of CCUS technology.
[0003] In the current CO2 capture process, the physical adsorption process using solid porous materials has the advantages of low difficulty in CO2 recovery, harmless recycling of adsorbents, and good matching of the CO2 adsorption and desorption temperature window with the flue gas environment. It is regarded as an important development direction for the next generation of low-cost, low-energy CO2 capture technology.
[0004] In the field of CO2 adsorption capture, the performance of adsorbent materials is still a key factor restricting the development of the process. The CO2 emission flux of industrial flue gas is large, but the concentration is low (10-20 vol%), which requires the adsorbent material to have high adsorption selectivity, large adsorption capacity and low regeneration energy consumption. However, the existing CO2 adsorbent materials often have difficulty in balancing adsorption capacity, adsorption selectivity and regeneration energy consumption.
[0005] Taking commercial carbon-based adsorbents as an example, the adsorption capacity and adsorption selectivity can be effectively improved by grafting polar functional groups. Related studies (J. Mater. Chem. A 2016, 4, 18248-18252; Carbon 2016, 109, 747-754) show that the introduction of less than 10at% of nitrogen / oxygen functional groups into carbon materials can increase the CO2 adsorption capacity by 1 times and the CO2 / N2 adsorption selectivity by 20-30 times. However, this improvement also brings significant problems: the introduction of polar functional groups will significantly increase the isosteric adsorption heat of CO2, resulting in a significant increase in regeneration energy consumption. It is calculated (Carbon 2024, 225, 119152) that when 5at% of polar functional groups are introduced into the carbon-based adsorbent, the isosteric adsorption heat of low-concentration CO2 will increase by more than 1 times, thereby increasing the CO2 capture cost by at least 30%.
[0006] The bottleneck of high energy consumption for polar adsorbent regeneration mainly comes from two aspects:
[0007] There is a strong quadrupole interaction between the polar functional groups of the polar adsorbent and CO2. Although this interaction can significantly improve the adsorption capacity and selectivity, it also requires high energy input to overcome this interaction during the regeneration process.
[0008] Second, CO2 is unevenly distributed in the polar adsorbent. CO2 is mostly concentrated near polar functional groups, while the traditional thermal regeneration method applies energy evenly to the adsorbent surface, resulting in high ineffective energy loss.
[0009] At present, it is difficult to solve the above two problems only by regulating the intrinsic physical and chemical structure of the adsorbent.
[0010] Therefore, how to achieve low-energy regeneration while improving CO2 adsorption capacity and adsorption selectivity has become a key technical problem that needs to be urgently solved in the development of low-cost flue gas CO2 adsorption capture technology. Summary of the invention
[0011] In order to solve the problems existing in the background technology, the present invention provides a CO2 adsorption and capture method based on the coupling of polar functional groups of carbon materials and electric fields.
[0012] To achieve the above object, the present invention adopts the following technical solution: a CO2 adsorption capture method based on the coupling of polar functional groups of carbon materials with electric fields, the method comprising the following steps:
[0013] S1: Directed grafting of polar functional groups onto carbon-based adsorbents;
[0014] S2: Evenly mix the carbon-based adsorbent obtained in S1 with quartz sand;
[0015] S3: placing the uniformly mixed carbon-based adsorbent and quartz sand in a fixed bed reactor, and adjusting the bed temperature and pressure to the required level;
[0016] S4: introducing industrial flue gas containing 10-20 vol% CO2 into a fixed bed reactor;
[0017] S5: Carbon-based adsorbents capture CO2;
[0018] S6: applying an external electric field to the carbon-based adsorbent after the carbon-based adsorbent is saturated with CO2;
[0019] S7: The carbon-based adsorbent is thermally regenerated, and the temperature of the thermal regeneration process is 80-150°C.
[0020] The pore size of the carbon-based adsorbent is less than 0.7 nm, and the pore volume of the carbon-based adsorbent is not less than 0.6 cm 3 / g.
[0021] The polar oxygen-containing functional group of the polar functional group described in S1 is one or more combinations of carboxyl, hydroxyl and carbonyl.
[0022] The polar oxygen-containing functional group content of the polar functional group in S1 is 5 to 15 at %.
[0023] The polar nitrogen-containing functional group of the polar functional group described in S1 is one or more combinations of pyridinic nitrogen, pyrrolic nitrogen, amino group, and graphitic nitrogen.
[0024] The polar nitrogen-containing functional group content of the polar functional group in S1 is 5 to 10 at %.
[0025] The operating temperature of the fixed bed reactor in S3 is 20-40°C.
[0026] S6 The external electric field is applied in the form of an external electromagnetic electrode, and the voltage of the electromagnetic electrode is 0.5-1.5V.
[0027] S6: The applied electric field is in the form of microwave irradiation, and the power of the microwave irradiation is 50-100W.
[0028] S6 The external electric field acts in the form of Joule heating, and the voltage of the Joule heating is 0.5-3V.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] The present invention strengthens the physical adsorption capacity of CO2 by grafting polar functional groups onto the surface of the adsorbent, realizes efficient energy focusing from point to surface, and improves the high selectivity and large-capacity adsorption performance of the adsorbent for CO2. It achieves efficient synergy between adsorption capacity, adsorption selectivity and regeneration energy consumption, and improves the overall energy efficiency of the CO2 adsorption and capture process. Furthermore, through the use of functional groups of specific types and contents and an external electric field of specific intensity, the energy is guided to be focused near the polar functional groups enriched in CO2, so that the adsorption points have the dual functions of CO2 aggregation and energy focusing, reducing invalid energy consumption. Compared with the currently widely used temperature and pressure swing adsorption method, while reducing invalid energy consumption, it realizes high-selectivity, large-capacity adsorption and low-energy regeneration of CO2, effectively breaking through the current technical bottleneck of synergy between efficient adsorption of CO2 and low-energy regeneration. During the adsorbent regeneration stage, the coupling effect of the external electric field and the polar functional groups promotes the efficient focusing of energy, offsets the interaction potential field between the polar functional groups and CO2, and enables the adsorbed CO2 to be desorbed quickly and with low energy consumption, thereby further improving the energy efficiency of the entire adsorption and capture process. DETAILED DESCRIPTION
[0031] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0032] A CO2 adsorption and capture method based on the coupling of polar functional groups of carbon materials with electric fields, the method comprising the following steps:
[0033] S1: Directed grafting of polar functional groups on carbon-based adsorbents to strengthen the quadrupole interaction between CO2 and carbon-based adsorbents, and achieve high-capacity and high-selectivity adsorption of CO2;
[0034] The pore size of the carbon-based adsorbent is less than 0.7 nm, and the pore volume of the carbon-based adsorbent is not less than 0.6 cm 3 / g.
[0035] The polar oxygen-containing functional group of the polar functional group is one or more combinations of carboxyl, hydroxyl and carbonyl.
[0036] The polar oxygen-containing functional group content of the polar functional group is 5 to 15 at %.
[0037] The polar nitrogen-containing functional group of the polar functional group is one or more combinations of pyridinic nitrogen, pyrrolic nitrogen, amino group and graphitic nitrogen.
[0038] The polar nitrogen-containing functional group content of the polar functional group is 5 to 10 at %.
[0039] S2: Evenly mix the carbon-based adsorbent obtained in S1 with quartz sand;
[0040] S3: placing the uniformly mixed carbon-based adsorbent and quartz sand in a fixed bed reactor, and adjusting the bed temperature and pressure to the required level;
[0041] The operating temperature of the fixed bed reactor is 20-40°C.
[0042] S4: introducing industrial flue gas containing 10-20 vol% CO2 into a fixed bed reactor;
[0043] S5: Carbon-based adsorbents capture CO2;
[0044] S6: After the carbon-based adsorbent is saturated with CO2, an external electric field is applied to the carbon-based adsorbent; during the regeneration process, the energy is directed to focus on the CO2-enriched area through the combination of the electric field and polar functional groups, while the electrostatic interaction between CO2 and the carbon-based adsorbent is offset, thereby achieving low-energy regeneration of CO2.
[0045] The external electric field is applied in the form of an external electromagnetic electrode, and the voltage of the electromagnetic electrode is 0.5-1.5V.
[0046] Or the external electric field is in the form of microwave irradiation, and the power of the microwave irradiation is 50-100W.
[0047] Or the external electric field acts in the form of Joule heating, and the voltage of the Joule heating is 0.5-3V.
[0048] S7: The carbon-based adsorbent is thermally regenerated, and the temperature of the thermal regeneration process is 80-150°C.
[0049] The carbon-based adsorbent grafted with polar functional groups is obtained through oxidant etching, catalytic activation of heteroatom-containing gas, and co-thermal conversion deposition of heteroatom-containing polymers. The type and content of polar functional groups grafted in the carbon-based adsorbent are regulated by regulating the temperature of the thermal conversion process and the type and content of heteroatom-containing polymers in the co-thermal conversion process.
[0050] The carbon-based adsorbent used in the present invention can be prepared at low cost using fuel coal from coal-fired power plants as raw materials, and polar functional group grafting can be achieved by utilizing flue gas environments such as NH3 and H2O from coal-fired power plants. The external electric field during the regeneration process can come from devices such as electrostatic precipitators.
[0051] The conditions required for the implementation of the present invention are highly compatible with the environment of coal-fired power plants, etc., and have significant cost advantages over the current CO2 adsorption capture technology.
[0052] Embodiment 1:
[0053] S1: A carbon-based adsorbent with polar functional groups directed grafted is prepared by oxidant etching combined with nitrogen-containing organic polymer deposition and co-thermal conversion. By adjusting the type and amount of the oxidant and nitrogen-containing organic polymer, the prepared carbon-based adsorbent contains 10% polar oxygen-containing functional groups and 8% polar nitrogen-containing functional groups;
[0054] S2: mixing the prepared carbon-based adsorbent and quartz sand evenly and placing them into a fixed bed reactor;
[0055] S3: A simulated flue gas with a concentration of 15% CO2 and a concentration of 85% N2 was introduced, and a CO2 adsorption capture experiment was carried out at 30°C;
[0056] S4: After the carbon-based adsorbent reaches adsorption saturation, an electromagnetic electrode with an external voltage of 1 V is connected to perform a thermal regeneration experiment at a temperature of 100 °C.
[0057] Experimental results:
[0058] The CO2 adsorption capacity is 1.5mmol / g, and the converted regeneration energy consumption is 1.24GJ / t CO2.
[0059] Embodiment 2:
[0060] The difference between this embodiment and embodiment 1 is that:
[0061] S4: After the carbon-based adsorbent reaches adsorption saturation, 100 W of microwave irradiation is applied and a thermal regeneration experiment is carried out at a temperature of 100 °C.
[0062] Experimental results:
[0063] The CO2 adsorption capacity is 1.5mmol / g, and the converted regeneration energy consumption is 1.05GJ / t CO2.
[0064] Embodiment 3:
[0065] The difference between this embodiment and embodiment 1 is that:
[0066] S4: After the carbon-based adsorbent reaches adsorption saturation, 2.5V Joule heating is applied for 5 minutes, and a thermal regeneration experiment is carried out at a temperature of 100°C.
[0067] Experimental results:
[0068] The CO2 adsorption capacity is 1.5mmol / g, and the converted regeneration energy consumption is 1.25GJ / t CO2.
[0069] Comparative experiment 1:
[0070] The difference between this comparative experiment and Example 1 is:
[0071] S1: The content of polar oxygen-containing functional groups in the carbon-based adsorbent is less than 5% and the content of polar nitrogen-containing functional groups is less than 3%;
[0072] Experimental results:
[0073] The CO2 adsorption capacity is only 0.5mmol / g, and the converted regeneration energy consumption is 0.88GJ / t CO2.
[0074] Comparative experiment 2:
[0075] The difference between this comparative experiment and Example 1 is:
[0076] Cancel S4 and do not add external electric field.
[0077] Experimental results:
[0078] The CO2 adsorption capacity is 1.5mmol / g, and the converted regeneration energy consumption is as high as 2.13GJ / t CO2.
[0079] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalents of the claims be included in the present invention.
[0080] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A CO2 adsorption capture method based on the coupling of polar functional groups of carbon materials with electric fields, characterized in that: The method comprises the following steps: S1: Directed grafting of polar functional groups onto carbon-based adsorbents; S2: Evenly mix the carbon-based adsorbent obtained in S1 with quartz sand; S3: placing the uniformly mixed carbon-based adsorbent and quartz sand in a fixed bed reactor, and adjusting the bed temperature and pressure to the required level; S4: introducing industrial flue gas containing 10-20 vol% CO2 into a fixed bed reactor; S5: Carbon-based adsorbents capture CO2; S6: applying an external electric field to the carbon-based adsorbent after the carbon-based adsorbent is saturated with CO2; S7: The carbon-based adsorbent is thermally regenerated, and the temperature of the thermal regeneration process is 80-150°C.
2. According to claim 1, a CO2 adsorption and capture method based on the coupling of polar functional groups of carbon materials and electric fields is characterized by: The pore size of the carbon-based adsorbent is less than 0.7 nm, and the pore volume of the carbon-based adsorbent is not less than 0.6 cm 3 / g.
3. The CO2 adsorption capture method based on the coupling of carbon material polar functional groups and electric field according to claim 2, characterized in that: The polar oxygen-containing functional group of the polar functional group described in S1 is one or more combinations of carboxyl, hydroxyl and carbonyl.
4. The CO2 adsorption capture method based on the coupling of carbon material polar functional groups and electric field according to claim 3 is characterized in that: The polar oxygen-containing functional group content of the polar functional group in S1 is 5 to 15 at %.
5. The CO2 adsorption capture method based on the coupling of carbon material polar functional groups and electric field according to claim 2, characterized in that: The polar nitrogen-containing functional group of the polar functional group described in S1 is one or more combinations of pyridinic nitrogen, pyrrolic nitrogen, amino group, and graphitic nitrogen.
6. The CO2 adsorption capture method based on the coupling of carbon material polar functional groups and electric field according to claim 5, characterized in that: The polar nitrogen-containing functional group content of the polar functional group in S1 is 5 to 10 at %.
7. The CO2 adsorption capture method based on the coupling of carbon material polar functional groups and electric field according to claim 1, characterized in that: The operating temperature of the fixed bed reactor in S3 is 20-40°C.
8. The CO2 adsorption capture method based on the coupling of carbon material polar functional groups and electric field according to claim 6, characterized in that: S6 The external electric field is applied in the form of an external electromagnetic electrode, and the voltage of the electromagnetic electrode is 0.5-1.5V.
9. The CO2 adsorption capture method based on the coupling of carbon material polar functional groups and electric field according to claim 6, characterized in that: S6: The applied electric field is in the form of microwave irradiation, and the power of the microwave irradiation is 50-100W.
10. The CO2 adsorption and capture method based on the coupling of polar functional groups of carbon materials and electric fields according to claim 6, characterized in that: S6 The external electric field acts in the form of Joule heating, and the voltage of the Joule heating is 0.5-3V.
